Distribution of pediatric keratoconus by different age and gender groups - Yang, Kaili; Gu, Yuwei; Xu, Liyan; Fan, Qi; Zhu, Meng; Wang, Qing; Yin, Shanshan; Zhang, Bo; Pang, Chenjiu; Ren, Shengwei (Frontiers in Pediatrics, 2022)
Purpose To evaluate the distribution of pediatric keratoconus patients and the disease severity based on different age and gender groups in China. Materials and methods A total of 446 keratoconus eyes in 266 pediatric patients from January 2019 to January 2022 were included in the cross-sectional study. The clinical findings and severity of keratoconus were recorded and Kruskal–Wallis test, chi-squared test, and Cochran-Mantel-Haenszel (CMH) test were used to compare the parameters between different gender and age groups. Results The male/female ratio was 353/93 (3.8:1), and the median age was 16 years (range: 6–17 years). Male patients were statistically younger than female patients (P = 0.041). The male/female ratio decreased with age (P for trend = 0.011). The distribution of the topographic keratoconus classification (TKC) stage was significantly different between gender and age groups (all P < 0.05). Male patients had a higher ratio of advanced keratoconus eyes (TKC ≥ 3) than female patients (P < 0.001), and CMH analysis indicated that being a male was a risk factor for advanced keratoconus after controlling for age (odds ratio: 2.581, P < 0.001). Conclusion Male keratoconus patients were younger, with a higher ratio of advanced keratoconus than female patients in the Chinese pediatric patients evaluated. Multicenter studies with larger sample sizes are necessary in the future.